Variation and disparity within the inner ear and trigeminus of the tenrecomorpha - R. Benjamin Sulser; Ross D. E. MacPhee (Communications Biology)
Abstract Evolutionary theory predicts that sensory systems should adaptively respond to environmental selection. Different ecological niches should, in theory, then correlate with changes in sensory anatomy in lineages that have undergone extensive radiation. The afrotherian clade Tenrecomorpha, comprising of African potamogalines and Malagasy tenrecines, is of particular interest because of its variety: the clade reportedly includes fossorial, arboreal, semiaquatic, and even echolocating taxa. To investigate their sensory ecology, we provide geometric morphometric analyses of inner ear endocasts of 24 tenrec species. We expand this dataset with 9 iodine-stained specimens to study trigeminal organization. Although tenrecomorphs display cross-taxon differences in sensory structures, our analyses distinguish signals of conflicting strength and direction within the tenrec ear, with no single factor that might explain a substantial portion of observed variation when accounting for phylogeny. This contrasts with prior studies of the tenrec cranial endocast, where sensory ecotype and habitat are strongly associated with shape. Iodine-enhanced scans of the trigeminal nerve align with this, and other studies based on bony anatomy. The disparate patterns of shape evolution in Tenrecomorpha and the contrasts exhibited by the inner ear and trigeminal nerve provide a nuanced portrait of neurosensory adaptation, differing from expectations set by other mammalian groups.